The Effect of Implementing a Project-Based Learning Model on Biology Learning Outcomes of Class XI Students at SMA Negeri 3 Gowa - Tenri Lalla, Putri Pati; Hala, Yusminah; Syamsiah, Syamsiah (Biology Teaching and Learning, 2024)
This research has two objectives, namely 1) to assess the biology learning outcomes of class XI students at SMA Negeri 3 Gowa after implementing a project-based learning approach. 2) Understand how project-based learning influences students' biology learning outcomes at SMA Negeri 3 Gowa XI. This research uses a pretest-posttest control group design. This research was attended by all Class XI MIA students of SMA Negeri 3 Gowa, totaling 241 students, including control and experimental classes. Sampling used simple random sampling. Data collection uses test instruments in 30 topic categories. Based on the data obtained after being given treatment, it shows different results, namely that the experimental class obtained an average learning outcome score of 83.33 which was higher compared to the average score of the control class, namely 59.89 and the application of the project-based learning model showed that there was an influence on the results. learning of class 0.000 < 0.05Key words: project based learning model, learning outcomes